Undokumentierte Migration in Deutschland und den Vereinigten Staaten - interne Migrationskontrollen und die Handlungsspielräume von Sans Papiers - Stobbe, Holk (Universitätsverlag Göttingen, 2004)
What are the effects of internal migration controls on migrants without a regular residence permit - on "sans papiers"? The book gives an answer to this question with a comparative study of the United States and Germany. Based on expert interviews and in-depth interviews with forty sans papiers, police controls as well as controls in areas such as labor market, health care, housing, schooling and childcare are carefully analysed. The book discusses whether global economic, political or social processes have restricted the ability of advanced capitalist countries to control migration. It argues that migration policy in the OECD countries has become more similar, but this convergence only takes place at the level of policy goals and legal norms. At the level of implementation, national differences persist. The interviews show that sans papiers in the U.S. continue to have many possibilities to participate in society. In contrast, the comprehensive exclusion of sans papiers in Germany confi rms that there is no general "loss of control".